Mie metasurfaces for enhancing photon outcoupling from single embedded quantum emitters - Prescott Samuel; Iyer Prasad P.; Addamane Sadhvikas; Jung Hyunseung; Luk Ting S.; Brener Igal; Mitrofanov Oleg (Nanophotonics)
Solid-state quantum emitters (QE) can produce single photons required for quantum information processing. However, their emission properties often exhibit poor directivity and polarisation definition resulting in considerable loss of generated photons. Here we propose and numerically evaluate Mie metasurface designs for outcoupling photons from an embedded and randomly-positioned QE. These Mie metasurface designs can provide over one order of magnitude enhancement in photon outcoupling with only several percent of photons being lost. Importantly, the Mie metasurfaces provide the enhancement in photon outcoupling without the need for strict QE position alignment and without affecting the intrinsic QE emission rate (Purcell enhancement). Electric dipole modes are key for achieving the enhancement and they offer a path for selective outcoupling for photons emitted with specific polarisation, including the out-of-plane polarisation. Mie metasurfaces can provide an efficient, polarisation-selective and scalable platform for QEs.